2008
DOI: 10.1523/jneurosci.4609-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Glial Dysfunction in Parkin Null Mice: Effects of Aging

Abstract: Parkin mutations in humans produce parkinsonism whose pathogenesis is related to impaired protein degradation, increased free radicals, and abnormal neurotransmitter release. The role of glia in parkin deficiency is little known. We cultured midbrain glia from wild-type (WT) and parkin knock-out (PK-KO) mice. After 18 -20 d in vitro, PK-KO glial cultures had less astrocytes, more microglia, reduced proliferation, and increased proapoptotic protein expression.PK-KO glia had greater levels of intracellular gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 96 publications
4
119
0
Order By: Relevance
“…Glutathione synthesis in neurons is dependent on the expression of the cystine/glutamate exchange transporter on astrocytes (Shih et al, 2006;Wang & Cynader, 2000). Other studies demonstrated that glutathione and its synthesis-related molecules provide protection for astrocytes against age-dependent nigrostriatal dopaminergic neuro-degeneration (Chinta et al, 2007;Solano et al, 2008). ZNS markedly increased glutathione levels by enhancing the astroglial cystine/glutamate exchange transporter and astroglial proliferation via S100β production or secretion.…”
Section: Enhancement Of Glial Glutathione Synthesismentioning
confidence: 99%
“…Glutathione synthesis in neurons is dependent on the expression of the cystine/glutamate exchange transporter on astrocytes (Shih et al, 2006;Wang & Cynader, 2000). Other studies demonstrated that glutathione and its synthesis-related molecules provide protection for astrocytes against age-dependent nigrostriatal dopaminergic neuro-degeneration (Chinta et al, 2007;Solano et al, 2008). ZNS markedly increased glutathione levels by enhancing the astroglial cystine/glutamate exchange transporter and astroglial proliferation via S100β production or secretion.…”
Section: Enhancement Of Glial Glutathione Synthesismentioning
confidence: 99%
“…51,52 The elevated levels of free radicals in absence of parkin could contribute to the amyloidosis. Other mechanisms though parkin could be involved in amyloid deposition, are the altered inflammatory response and elevated microglial levels observed in absence of parkin [82][83][84] which have been extensively implied in AD 85 and are also observed in the PK -/-/Tau VLW mice model. 51 This model suggests that parkin could be a link between tau and amyloid deposition, the two most important pathogenic mechanisms in AD.…”
Section: Parkin and Amyloidosismentioning
confidence: 99%
“…Apoptosis was measured by light microscopy, DNA staining with bis-benzimide (Hoechst 33342) and the TUNEL assay [16,28,29]. Necrosis was measured according to lactate dehydrogenase activity [30] in the culture medium and by trypan blue dye exclusion in cells [29].…”
Section: Cellular Characterization and Viability Anti-oxidants And Pmentioning
confidence: 99%
“…But parkin null cells are more susceptible to additional insults such as treatment with rotenone, a mitochondrial toxin [14], calcium channel antagonists, such as cinnarizine [15] or to the effects of aging, when the supportive function of glia is reduced and the increased production of GSH collapses [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation